Virginia Woolf's new intellectualism in relation to the construction of a third gender based on desire in her selected works - Montashery, Iraj (2012)
In A Room of One’s Own (1929), Virginia Woolf subversively urges that “we think back through our mothers if we are women” (132); this radical belief which was uncommon in Woolf’s time turned out to be her lifelong commitment in her literary life, and which formulated a new form of intellectualism. This thesis explores Woolf’s radical argument in locating subjectivity in relation to desire: the desire to return to the lost mother, whose absence is the source and initiator of all speech and writing, and that which removes the values drawn by patriarchal maxims in reference to subjectivity. This new intellectualism specifically connects subjectivity to femininity, and considers the semiotic as doubly important in the construction of identity. The inscription of desire from a subject position particularly for female characters is a way of constituting a differently gendered self, which ultimately leads to the representation of female characters as the subjects of desire, and not the objects of male desire. In this study I will use the psychoanalytic approaches of Jacques Lacan and Julia Kristeva to juxtapose the symbolic and the semiotic, so as to not emphasise one over the other. These approaches valorise and celebrate the semiotic, to foreground its significance in the construction of identity. Furthermore, the inscription of desire for the maternal space takes multiple and plural systems of signification, and comes closer to the French feminists’ écriture féminine, which is informed by the semiotic, and is able to disrupt, undermine and circumvent phallocentric symbolic language. In my exploration of the ways in which desire informs textuality, I will focus on Woolf’s Mrs Dalloway (1925), To the Lighthouse (1927) and The Waves (1931), and show, by way of écriture féminine, how desire acts both as a subversive element—which is by no means reducible to any patriarchal expectations or definitions regarding the trajectory of subjects’ sexual orientations—and as a defining element in disrupting and disturbing the commonly conceived and accepted binary thinking on sexuality. The latter opens up the possibility of a third gender, and consequently a new subject position in between the semiotic and the symbolic, which is the sum total of both; this grants the female subjects a hitherto denied agency.